Quantification of dose uncertainties in cumulated dose estimation compared to planned dose in prostate IMRT. Issue 1 (April 2016) - Nassef, Mohamed; Simon, Antoine; Cazoulat, Guillaume; Duménil, Aurélien; Blay, Christophe; Lafond, Caroline; Acosta, Oscar; Balosso, Jacques; Haigron, Pascal; de Crevoisier, Renaud
Abstract: Background and purpose: In prostate IMRT, the objectives were to quantify, for the bladder and the rectum: (i) the dose difference (DD) between the planned dose (PD) and the estimated cumulated dose (ECD) by deformable image registration (DIR); (ii) the dose accumulation uncertainties (DAU). Materials and methods: A series of 24 patients receiving 80 Gy in the prostate was used to calculate the ECDpts and the DDpts . To evaluate the DAU, a numerical phantom (ph) simulating deformations of main pelvic organs was used to calculate the ECDph using the same DIR method. A reference cumulated dose (RCDph ) was calculated, based on the simulated deformations. The DAUph was defined by the differences between RCDph and ECDph . Results: For the mean dose to the bladder, the standard deviation of DDpts was 6.9 Gy (18.1 Gy maximum) with a DAUph of 2.7 Gy. For the rectum wall, it was 2.0 Gy (4.2 Gy maximum) with a DAUph of 1.2 Gy. Volume differences between PDpts and ECDpts, along the dose–volume histogram, ranged from −30% to +37% and −14% to +14% for the bladder and rectum, respectively. The corresponding uncertainties ranged from −23% to +7% and −4% to +7% for the bladder and rectum, respectively. Conclusions: Large differences between planned and delivered doses to the bladder have been quantified and are higher than the uncertainties of the DIR method. For the rectum, the differences are smaller and close to the DIR uncertainties.